AMBIDEXTERITY OF PUBLIC SECTOR LEADERSHIP: SYNTHESIS OF TRANSACTIONAL AND TRANSFORMATIONAL MODELS TOWARDS ADAPTIVE BUREAUCRACY IN THE VUCA ERA (CASE STUDY OF THE SIKKA REGENCY GOVERNMENT) - Adrianus F Parera; Hendrik Toda; Melkisedek N B C Neolaka; Maria L Lino (RADJA PUBLIKA, 2026)
The dynamics of the VUCA ( Volatile, Uncertain, Complex, Ambiguous ) era characterized by regulatory uncertainty, regional fiscal limitations, and service disruptions demand responsive governance. This study aims to analyze the application of adaptive leadership through a synthesis of transactional and transformational models in the Sikka Regency Government by integrating aspects of local work culture. The research method used is a mixed methods quantitative descriptive method strengthened by a qualitative approach through in-depth interviews with key informants. The results of data collection indicate significant differences in perception: the Regional Secretary group assesses the transactional (4.2), transformational (4.6), and adaptive (4.7) leadership dimensions as High, while the Head of Regional Apparatus assesses transactional leadership as Medium (3.8). This empirical contrast is rooted in the strong paternalistic culture of the bureaucracy and the bias in implementing the Kula Babong tradition . This article formulates the reconstruction of Ambidextrous Public Leadership , where adaptive leaders in Sikka Regency are required to synthesize formal administrative compliance (transactional) with deliberative work culture transformation (transformational) so that organizational agility can be optimally accelerated. [ 1 , 2 , 3 , 4 , 5 ]